Pengaruh Panjang Tes dan Ukuran Contoh pada Pendugaan Parameter Model IRT - Hasanah, Siti; Pomalingo, Dewi Zulyani; Kurnia, Anang; Dwinata, Alona (SAP (Susunan Artikel Pendidikan), 2024)
IRT (Item Response Theory) can explain the relationship between a person's response to an item and a latent variable (ability). The number of items or exercise questions given by an elementary to high school teacher is usually not very large. The same goes for the number of students, who are usually divided into different classes, ranging from 30 to 35 students per class. This study was conducted in June 2023 and aims to determine the influence of sample size and test length on the estimation of parameters in the item response theory (IRT) 1 PL model with small-sized data. The parameters analyzed through the IRT 1 PL model include item parameters, namely difficulty, and ability parameters. The data were obtained from generation of simulation results. Data generation simulations with several scenarios were used to construct the IRT 1 PL model, based on test lengths (10, 15, 20) and sample sizes (32, 64). The research results are indicated by the closeness of the estimated parameter ? (ability) to the true parameter, which increases as the test length increases. When the test length is considered constant, the closeness of the estimated difficulty parameter increases with an increase in the sample size in small-scale scenarios.